PENGARUH KEPUASAN KERJA TERHADAP KUALITAS LAYANAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI PADA SOPIR PT. LOMBOK TAKSI - Eko Setia Budi; Surati Surati; Sri Wahyulina (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
The growth of online taxi service recently becomes the threats for PT Lombok Taksi to still survive against the competition in the business this research is aimed at analyzing the significant effect of work satisfaction on the service quality of drivers of PT Lombok Taksi, at analyzing the significant effect of work satisfaction on organizational commitment, at analyzing the significant effect of organizational commitment on service quality of drivers PT Lombok Taksi. This research is associative-causal the population is all 532 drivers of  Lombok Taksi from which 84 samples (rounded to 100) were selected as respondents by applying the Slovin formula. The samples were selected through propotional random sampling technique. The hypothesis test was conducted using path analysis using SPSS program version 16.00 for windows.Keywords : work satisfaction, organizational commitment, service quality.